2020
DOI: 10.3390/a13060134
|View full text |Cite
|
Sign up to set email alerts
|

Study of Quasi-Static Magnetization with the Random-Field Ising Model

Abstract: The topic of this paper is modeling based on Hamiltonian spin interactions. Preliminary studies on the identification of quasi-static magnetizing field in a magnetic system were presented. The random-field Ising model was then used to simulate the simplified ferromagnetic structure. The validation of algorithms and simulation tests were carried out for the 2D and the 3D model spaces containing at least 106 unit cells. The research showed that the response of a slowly driven magnetic system did not depend on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Quasi-static excitation conditions were checked using the classification criterion discussed in detail in Ref. [31]. More details on the measurement setup developed by one of the authors may be found in Ref.…”
Section: Measurementsmentioning
confidence: 99%
“…Quasi-static excitation conditions were checked using the classification criterion discussed in detail in Ref. [31]. More details on the measurement setup developed by one of the authors may be found in Ref.…”
Section: Measurementsmentioning
confidence: 99%
“…The Ising model is primarily used for the analysis of phase changes [13][14][15]. Its initial application was in statistical mechanics and phase transitions in the magnetism model [16]. The Potts model [17] is the generalization of the Ising model, allowing more than two states to be considered, which widened the area of use.…”
Section: Introductionmentioning
confidence: 99%
“…However, these solutions do not take into account the actual methods of collecting information about the current state of traffic. Only in [16], attention was paid to collecting basic data from sensors mounted on the road, but it was limited to information about the number of vehicles, and not about the direction of travel or the type of vehicle. This is especially important in the case of lanes that can be used for driving in different directions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this phenomenon is critical. One of the models allowing the analysis of phase transitions is the Ising magnetism model [5][6][7][8][9][10][11] and its generalisation in the form of the Potts model [12][13][14]. The potential of this model in studying the behaviour and properties of IT structures was presented in the author's earlier study [15].…”
Section: Introductionmentioning
confidence: 99%